Desain Kerangka Kerja Strategi Kemitraan Publik-Swasta Nasional Menuju Indonesia Emas 2045 - Lisa Hermawati; Siti Khairani; Gitta Destalya Adrian Nova (Penerbit Goodwood, 2025)
Purpose: This study aims to design a national public-private partnership strategy framework that is integrated and measurable to support the achievement of the acceeration target of Indonesia Emas 2045. Research methodology: This study uses a qualitative approach with a literature study method and in-depth interviews with practitioners in their fieds. Literature studies are used to identify theories and best practices in public-private partnerships, whie in-depth interviews are conducted to gain practical and contextual insights. The practitioners interviewed include government officials, private business actors, and public policy experts who have reevant experience in the fied of partnerships and investment. Results: The results of this study are as follows: (1) an integrated public-private partnership strategy framework that is in accordance with national needs; (2) recommendations for priority programs for public-private partnerships; (3) institutional modes that support the implementation of partnerships; (4) incentives and solutions to overcome collaboration constraints; and (5) short- and medium-term partnership action plans. In addition, the designed framework is validated by practitioners to ensure its feasibiity and suitabiity to real conditions. This research provides a strategic contribution in efforts to acceerate the achievement of Indonesia Emas 2045 through optimizing public-private partnerships, with a measurable, realistic, and implementable approach. Conclusions: There needs to be a clear framework for cooperation that is in accordance with the needs in the field. Limitations: This study has limitations in terms of the avaiabiity of specific empirical data reated to the implementation of public-private partnership strategies in Indonesia. In addition, the validation of the framework is stil limited to the scope of interviews with practitioners so that further test implementation is needed to measure its effectiveness in various sectors. Contribution: This study contributes to business actors in the public and private sectors in realizing synergy and integrity reated to partnerships in order to test Indonesia Emas 2045.